(3GdESJQGJjLjI hGdJSjjQ GdeGdj (B/s - (3edjcGhj, ehdhOs ((3GdLRGFQ(B: s (3OGQ gheI ddWHGYI hGdfTQ hGdJhRjY(B, s, 2018)
(3YGdL GdcGJH ehVhY GdGSJQGJjLjI hGdJSjjQ GdeGdj ef NdGd HGHjf QFjSjjf, MjK jMJhj GdHGH GdChd Ydi (B13 (3aUdG eYfhfG cGdBJj(B: ((3GdSjGSI GdeGdjI, GdGSJQGJjLjI GdeGdjI ddeDSSI, GdJTNjU GdGSJQGJjLj ddhVYjI GdeGdjI ddeDSSI , GdebGjjS GdMOjKI aj Jbjje GdCOGA GdeGdj, GdeDTQGJ GdeGdjI hGSJQGJjLjGJ GdeDSSI, JMdjd GdJOabGJ GdeGdjI hCHYGOgG GdGSJQGJjLjI, JcdaI GdJehjd hGgejJgG GdGSJQGJjLjI, GdbQGQGJ GdeGdjI GdGSJQGJjLjI hCKQgG aj JMOjO GdNjGQ GdGSJQGJjLj, GdbQGQGJ GdJehjdjI GdGSJQGJjLjI hCKQgG Ydi bjeI GdeDSSI, GdfXQjGJ GdeaSQI dJCKjQ Gdgjcd GdeGdj Ydi bjeI GdeDSSI, BdjGJ GdGNJjGQ GdESJQGJjLj ddgjcd GdeGdj, GSJQGJjLjGJ GdEOGQI GdeGdjI ddMO ef eNGWQ GdJYKQ GdeGdj, hGNjQG EOGQI GdeTJbGJ GdeGdjI(B) (3, CeG GdHGH GdKGfj abO bSe Edi (B10 (3aUhd eYfhfI cGdBJj (B: ((3eaghe GdJMdjd GdeGdj, GdbhGFe GdeGdjI GdeSJNOeI aj GdJMdjd GdeGdj, GdJMdjd GdeGdj HGSJNOGe GdfSH GdeGdjI, GdJMdjd GdeGdj GdOjfGejcj, GdCQUOI GdhSjWI ddJSjjQ , eNWW GdJehjd , GdejRGfjI GdhXjajI, GdGMJjGL aj QCS GdeGd GdYGed GdeYjGQj, GdbOQI Ydi GdJehjd GdPGJj, JSjjQ eNGWQ GdGSJKeGQ GdeGdj(B) s
(3GdeQGLY U(B.347s
Keywords: (3GdESJQGJjLjI GdeGdjIs; (3eGdjI GdeDSSI s